Four ideal-type organizational responses to new public management reforms and some consequences - Hernes, Tor (2005)
With its dual focus on service and accountability, New Public Management (NPM) accentuates the inherent tension between the logics of service and accountability respectively in local public administration. The present article explores, from an organization theory perspective, possible organizational responses to tensions created by the introduction of NPM. First, paralysis, whereby unresolved conflict leads to a stand-off situation between management and staff. Second, ritualistic decoupling, in the sense of decoupling between espoused and enacted practices. Third, loose coupling between functions and individuals. Fourth, organic adaptation, whereby the tension is handled constructively through internal structural and cultural differentiation. Possible causes and consequences of each of these responses for management are discussed. - Reproduced.
Keywords: Management; Organizations; Public administration; Administrative reform